THE VIABILITY OF ISSUE RECONCEPTUALIZATION IN THE ARAB-ISRAELI CONFLICT - Bergmann, Amanda (European Scientific Journal, ESJ, 2013)
The Israeli-Palestinian conflict is one of the most notorious intractable conflicts of the century. Historically, two streams of thought have dominated the academic realm of conflict resolution and reconciliation efforts: those which focus on reconciling final status issues, and those which focus on reconceptualizing identity. However, what has been neglected is the relationship between the two, or how identity affects individual’s perspectives on final status issues. As such, I propose that through re-conceptualization of issues, perspectives can be altered in such a way so that final status issues are no longer viewed as zero-sum. Such a re-conceptualization subsequently lays the foundations for more effective reconciliation and resolution efforts as both sides can envision potential gains. While this in itself is not an all-encompassing solution due to the dynamism of the conflict, when used in conjunction with other methods it provides yet another opportunity for open discussion and debate concerning resolution and reconciliation.